Endostatin inhibits VEGF-A induced osteoclastic bone resorption in vitro - Sipola, Annina (BioMed Central, 2006)
BACKGROUND: Endostatin is a C-terminal fragment of collagen XVIII which is a component of basement membranes with the structural properties of both collagens and proteoglycans. Endostatin has a major role in angiogenesis which is intimately associated with bone development and remodeling. Signaling between the endothelial cells and the bone cells, for example, may have a role in recruitment of osteoclastic precursor cells. Our study aims at exploring a possibility that endostatin, either as a part of basement membrane or as a soluble molecule, may control osteoclastogenesis and osteoclastic bone resorption in vitro. METHODS: Rat pit formation assay was employed in order to examine the effect of endostatin alone or in combination with vascular endothelial growth factor-A (VEGF-A) on bone resorption in vitro. Effect of these agents on osteoclast differentiation in vitro was also tested. Osteoclastogenesis and the number of osteoclasts were followed by tartrate resistant acid phosphatase (TRACP) staining and resorption was evaluated by measuring the area of excavated pits. RESULTS: Endostatin inhibited the VEGF-A stimulated osteoclastic bone resorption, whereas endostatin alone had no effect on the basal resorption level in the absence of VEGF-A. In addition, endostatin could inhibit osteoclast differentiation in vitro independent of VEGF-A. CONCLUSION: Our in vitro data indicate that collagen XVIII/endostatin can suppress VEGF-A induced osteoclastic bone resorption to the basal level. Osteoclastogenesis is also inhibited by endostatin. The regulatory effect of endostatin, however, is not critical since endostatin alone does not modify the basal bone resorption.